Development and Feasibility Testing of Digital Measurement Tools for the Height of Uterine Fundus - Mutiah, Mar'atu; Fatmasari, Diyah; Sumarni, Sri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Uterine Fundus Height (TFU) is an indicator for monitoring fetal well-being during pregnancy. So far, TFU measurements are still carried out manually with several weaknesses such as human error, takes a long time, and less efficiency, which requires new innovations. This study aims to develop a tool for measuring uterine fundal height by utilizing an artificial intelligence-based rotary encoder sensor to determine gestational age and estimated fetal weight. Subjects and Method: This study used Research and Development (R&D) in the R&D stage with stages carried out at the Adem Ayem Clinic from January to February 2023. Expert validation testing and small-scale product trials. A total of 10 pregnant women were selected in this study, they were divided into two groups: (1) Five pregnant women using a digital TFU measuring instrument; and (2) Five pregnant women used a measuring tape. The dependent variables are uterine fundal height, gestational age and estimated fetal weight. The independent variable is a tool for measuring uterine fundal height. Differences in TFU in the intervention and control groups were analyzed using the Mann Whitney test. Results: Development of a tool for measuring uterine fundal height that provides feasible and valid results in measuring uterine fundal height and determining gestational age and estimating fetal weight. Conclusion: Development of a tool for measuring uterine fundal height that provides feasible and valid results in measuring uterine fundal height and determining gestational age and estimating fetal weight. Keywords: uterine fundal height, gestational age, estimated fetal weight, rotary encoder sensor, pregnant women. Correspondence: Mar’atu Mutiah. Applied Masters Program, Health Polytechnic, Ministry of Health Semarang. Jl. Tirto Agung, Pedalangan, Banyumanik, Semarang, 50239, Central Java, Indonesia. Email: mara220792@gmail.com.